WWOX Tumor Suppressor Gene in Breast Cancer, a Historical Perspective and Future Directions - Pospiech, Karolina; Płuciennik, Elzbieta; Bednarek, Andrzej K. (Frontiers in Oncology, 2018)
The WWOX tumor suppressor gene is located at 16q23.1-23.2, which covers the region of FRA16D – a common fragile sites. Deletions within the WWOX coding sequence are observed in up to 80% of breast cancer cases, which makes it one of the most common genetic alterations in this tumor type. The WWOX gene is known to play a role in breast cancer: increased expression of WWOX inhibits cell proliferation in suspension, reduces tumor growth rates in xenographic transplants, but also enhances cell migration through the basal membrane and contributes to morphological changes in 3D matrix-based cell cultures. The WWOX protein may act in several ways, as it has three functional domains – two WW domains, responsible for protein-protein interactions and an SDR domain (short dehydrogenase/reductase domain) which catalyses conversions of low molecular weight ligands, most likely steroids. In epithelial cells, WWOX modulates gene transcription through interaction with p73, AP-2γ and ERBB4 proteins. In steroid hormone-regulated tissues like mammary gland epithelium, the WWOX SDR domain acts as a steroid dehydrogenase. The relationship between WWOX and hormone receptors was shown in an animal model, where WWOX(C3H)+/-mice exhibited loss of both ER and PR receptors. Moreover, in breast cancer specimens, a positive correlation was observed between WWOX expression and ER status. On the other hand, decreased WWOX expression was associated with worse prognosis, namely higher relapse and mortality rates in BC patients. Recently, it was shown that genomic instability might be driven by the loss of WWOX expression. It was reported that WWOX plays role in DNA damage response (DDR) and DNA repair by regulating ATM activation through physical interaction. A genome caretaker function has also been proposed for WWOX, as it was found that WWOX sufficiency decreases homology directed repair (HDR) and supports non-homologous end-joining (NHEJ) repair as the dominant DSB repair pathway by Brca1-Wwox interaction. In breast cancer cells, WWOX was also found to modulate the expression of glycolysis pathway genes, through hypoxia-inducible transcription factor 1α (HIF1α) regulation. The paper presents the current state of knowledge regarding the WWOX tumor suppressor gene in breast cancer, as well as future research perspectives.